A case of a massive desmoplastic fibroblastoma on the mandibular gingiva. Issue 2 (March 2023) - Yasuda, Takuji; Amano, Katsuhiko; Kawamura, Kohei; Cho, Jungsoo; Kogo, Mikihiko; Tanaka, Susumu
Abstract: Desmoplastic fibroblastoma (DF) is a rare benign fibrous soft tissue tumor that occurs in the subcutaneous and skeletal intramuscular tissue of the neck, shoulders, upper and lower limbs. Only a few cases of DF have been reported in the oral cavity so far. In this report, we describe a massive DF that occurred on the right mandibular gingiva of an 83-year-old woman. The imaging evaluation with X ray, CT and ultrasound (US) suggested a benign gingival tumor and excluded a possible malignancy. The incisional biopsy result was consistent with this observation and gave a histological diagnosis of fibrous gingival hyperplasia. Subsequently, the tumor was completely removed by surgery under intravenous sedation. HE staining revealed abundant collagenous fibers and spindle type fibroblasts in the tumor. Immunohistochemical analysis for vimentin, factor XⅢa and α-smooth muscle actin (αSMA) was positive, but Cytokeratin AE1/AE3, CD34 and S-100 results were negative. Therefore, we diagnosed the tumor as DF and the patient has a good prognosis. There has been no recurrence. Our report will provide important clinical information regarding rare benign soft tissue tumors in the oral cavity.